Rancang Bangun Aplikasi Sistem Pakar Menggunakan Metode Forward Chaining untuk Mendiagnosa Penyakit pada Ayam - Hasanah, Novi Aswatun; Rodianto, Rodianto; Yuliadi, Yuliadi (Universitas Multi Data Palembang, 2025)
This research aims to design and implement a web-based expert system using the Forward Chaining method to diagnose poultry diseases in Penyaring Village, Moyo Utara District, Sumbawa Regency. The system is intended to help poultry farmers diagnose diseases in their chickens independently by selecting observed symptoms and receiving accurate diagnoses and solutions. The system employs the Forward Chaining method, which matches the input symptoms with rules in the knowledge base to deduce the possible diseases and appropriate solutions. The implementation of the system shows that it can accurately diagnose poultry diseases based on user-selected symptoms. Additionally, the system provides relevant solutions for disease management, including vaccination, biosecurity, and treatment. With its user-friendly interface, the system enables farmers to access diagnostic information without needing expert assistance. Black box testing confirms that all system features function as expected. The system can be used by administrators to manage disease data, symptoms, and rules, and by farmers to perform diagnoses and obtain solutions. This research aims to improve poultry health in areas with limited veterinary services.